Determination of Urinary Biomarkers for Assessment of Short-Term Human Exposure to Aflatoxins in São Paulo, Brazil - Alessandra V. Jager; Fernando G. Tonin; Pollyana C. M. C. Souto; Rafaela T. Privatti; Carlos A. F. Oliveira (Toxins, 2014)
In the present study, a longitudinal assessment was carried out to evaluate the short-term human exposure to aflatoxins in Pirassununga region, São Paulo, Brazil, by determination of urinary aflatoxins by a liquid chromatography coupled to mass sprectrometry (UPLC-MS/MS) method. Sixteen volunteers with ages ranging from 14 to 55 years old were instructed to collect the early morning first urine four times every three months, from June 2011 to March 2012, totaling 64 samples. Aflatoxin M1 (AFM1) was found in 39 samples (61%) at levels ranging from 0.19 to 12.7 pg·mg−1 creatinine (mean: 1.2 ± 2.0 pg·mg−1 creatinine). Residues of aflatoxins B1, B2, G1, G2 and aflatoxicol were not identified in any urine sample. No significant difference was found among the AFM1 mean levels in urine samples collected in the four sampling periods. The levels of AFM1 found in urine samples indicate a low short-term exposure of the population studied to aflatoxins through the diet, although further investigations are needed to assess other long-term biomarkers of exposure to AFB1.